Effect of information sharing in supply chains: understanding the roles of supply chain visibility, agility, collaboration on supply chain performance - Baah, C.; Agyeman, D.O.; Acquah, I.S.K.; Agyabeng-Mensah, Y.; Issau, K.; Faibil, D. (Emerald Publishing Limited, 2021)
Purpose – Exploring ways to acquire, sustain and improve competitive positions in supply chains through information sharing, supply chain visibility, collaboration and agility have been essential for scholars and practitioners. Basing on the relational view, resource based view and the extended resource based view, this study assesses the critical role of information sharing in supply chains through emphasizing its effect on supply chain visibility, collaboration, agility and supply chain performance. Particularly, the study proposes that information sharing, supply chain visibility, collaboration and agility collectively have crucial direct and indirect influences on supply chain performance which lead to superior gains, competitiveness and flexibility. Design/methodology/approach – The study adopted a survey research design, a quantitative approach and partial least square structural equation modeling (PLS-SEM) in making data analysis and interpretations due to its suitability for predictive research models. Findings – The results indicate information sharing positively and significantly influenced supply chain visibility, collaboration, agility and performance. Supply chain visibility presented significant effects on collaboration, agility and performance, while supply chain collaboration and agility had significant impact on supply chain performance. The study findings connote that information sharing is key to enhancing competitive gains and superior supply chain performance. Originality/value – The study is among the few to probe on how information sharing as a variable interacts with supply chain visibility, collaboration, agility and performance. Although, information sharing has received a lot of attention in supply chains, this study is among the first to capture the study variables in a single model and thus, exposes the vital need for information sharing in improving supply chain performance seeing that it ensured significant and robust impacts on the study variables. Keywords Information sharing, Supply chain visibility, Supply chain collaboration, Supply chain agility, Supply chain performance, PLS-SEM
Research Article
Keywords: Information sharing; Supply chain visibility; Supply chain collaboration; Supply chain agility; Supply chain performance; PLS-SEM